![\frac{y}{ (x-y)^{2} } \frac{y}{ (x-y)^{2} }](https://tex.z-dn.net/?f=+%5Cfrac%7By%7D%7B+%28x-y%29%5E%7B2%7D+%7D+)
-
![\frac{x+y}{y^{2} -xy} \frac{x+y}{y^{2} -xy}](https://tex.z-dn.net/?f=+%5Cfrac%7Bx%2By%7D%7By%5E%7B2%7D+-xy%7D+)
=
![\frac{y*y}{ y(x-y)^{2} } \frac{y*y}{ y(x-y)^{2} }](https://tex.z-dn.net/?f=+%5Cfrac%7By%2Ay%7D%7B+y%28x-y%29%5E%7B2%7D+%7D+)
-
![image](https://tex.z-dn.net/?f=+%5Cfrac%7B%28x%2By%29%28x-y%29%7D%7By%28x-y%29%C2%B2%3Cspan%3E%7D+)
} " alt=" \frac{(x+y)(x-y)}{y(x-y)²
} " align="absmiddle" class="latex-formula"> =
^{2}-(x+y)(x-y)}{ y(x-y)(x-y)} " alt=" \frac{y
^{2}-(x+y)(x-y)}{ y(x-y)(x-y)} " align="absmiddle" class="latex-formula"> =
![image](https://tex.z-dn.net/?f=+%5Cfrac%7By%5E%7B2%7D-x%5E%7B2%7D%2By%5E%7B2%7D%3Cspan%3E%7D%7B+y%28x-y%29%28x-y%29%C2%A0%7D+)
}{ y(x-y)(x-y) } " alt=" \frac{y^{2}-x^{2}+y^{2}
}{ y(x-y)(x-y) } " align="absmiddle" class="latex-formula"> =